Histological transformation into SCLC: An important resistance mechanism of NSCLC upon immunotherapy - Zeng, Jiao; Ding, Xinjing; Ding, Jianghua; Wang, Xin (Frontiers in Immunology, 2023)
The phenomenon of histological transformation has been widely reported in advanced non-small cell lung cancer (NSCLC) with EGFR mutations following the failure of EGFR-TKI treatment. Recent evidence suggests that similar histological changes can also occur in advanced NSCLC without driver gene mutations after developing resistance to immunotherapy. In this review, it was found that 66.7% of cases with immunotherapy-induced histological transformation were classified as lung squamous cell carcinoma (LSCC), while histological conversion into lung adenocarcinoma (LUAD) without EGFR or ALK gene mutations has rarely been reported. There have been sporadic reports on the occurrence of mutual transformation between LUAD and LSCC. The histological conversion from NSCLC into small cell lung cancer (SCLC) appears to be significantly underestimated, likely due to the infrequency of re-biopsy following the development of immunotherapy resistance. Several studies have reported a close association between the transformation and mutations at TP53 and the RB1 splice site, as well as the loss of an FBXW7 mutation. However, the exact mechanisms underlying this conversion remain unclear. Currently, there is a lack of guidelines for the management of transformed SCLC from NSCLC following immunotherapy, with chemotherapy being the most commonly employed treatment approach.